Revisiting the Interplays of Sound, Meaning, Education 23 - edwards, jashen; Rinsema, Rebecca (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2026)
In their editorial for this issue, “Revisiting the Interplays of Sound, Meaning, Education 23,” jashen edwards and Rebecca Rinsema explain: "Drawing upon a range of research methodologies, conceptual framings, and artistic practices, SME 23 nurtured a space for scholarship promoting exploration, curiosity, and dialogue. From improvisational games inviting musical creativity to sonic art integrating experimental electronics, puppetry, and AI visuals; from hearing newly designed musical instruments to listening to local ambience on a semi-guided soundwalk—SME 23 provided multisensory participation. The energy over those three days was infectious. An obvious next step was to engage in another collaboration: between SME and Critical Studies in Improvisation / Études critiques en improvisation."